A low-cost long-term model of coastal observatories of global change. Issue 1 (2nd January 2019) - Sanchez-Cabeza, Joan-Albert; Álvarez Sánchez, León Felipe; Cardoso-Mohedano, José Gilberto; Escalante Mancera, Edgar; Díaz-Asencio, Misael; López-Rosas, Hugo; Machain-Castillo, Maria Luisa; Merino-Ibarra, Martín; Ruiz-Fernández, Ana Carolina; Alonso-Rodríguez, Rosalba; Gómez-Ponce, Mario Alejandro; Ávila, Enrique; et al.
ABSTRACT: The identification and quantification of global change, including climate change, requires long time series of key variables. In this work, the fundamentals and operation of low-cost long-term coastal observatories are described, and preliminary data are shown. The vision is to offer a scientific platform of physicochemical data for at least the next 100 years, what requires establishing sustainable strategies, training human resources, strong institutional support, and long-term funding sources. The network formally operates since 2013 and has generated more than 6 million data points, continuously growing, of which >1.5 million data points are permanently stored and available through a public access web platform. The strategies and methodologies are described and, in the Mazatlan observatory, data recovery and basic statistics of eight environmental variables are presented. During 2015, an extreme El Niño year, marine temperatures increased from the bay to the middle Urias coastal lagoon, were higher than atmospheric temperatures, and showed the impact of a thermal power plant. In surface waters of Mazatlan bay, hypoxic periods were also observed. It is expected that results will foster the development of other projects, and will be useful to the scientific community and decision makers, for a better management of coastal ecosystems worldwide.